Economic benefit from the optimization of citric acid production from rice straw through Plackett-Burman design and central composite design - Hayder Khaleel, Qurban Ali; Mohamed Zulkali, Mohamed Daud; Zinah, Al-Azzawi (TÜBİTAK., 2013)
Link to publisher's homepage at http://www.tubitak.gov.tr/